SOSIALISASI QANUN JINAYAT ACEH NO. 6 TAHUN 2014 PADA MADRASAH ALIYAH BLANGKEJEREN KABUPATEN GAYO LUES - Misran Misran (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2019)
There are two questions in the study under study, namely: First, what is the knowledge and understanding of students in Gayo Lues District Madrasah Ali about the implementation of the Jinayat Aceh Qanun Number 6 of 2014? Secondly, What is the knowledge and role of the Gayo Lues District Madrasah Aliyah religious teacher in disseminating to students about the enactment of the 2014 Jinayat Aceh Qanun? This study uses a normative juridical and sociological juridical approach. The normative juridical approach is done by first examining the Aceh regulation or qanun that is relevant to the problem under study. In other words the normative approach is to examine library materials or secondary data which includes primary, secondary and tertiary legal materials. The results showed that Gayo Lues State students in general knew about the implementation of Islamic Shari'a in Aceh, but the majority of them did not know and understand about the material regulated in Aceh No. 3 Qanun. 6 of 2014. Especially they do not know and understand about the terms contained in the Aceh jinayat qanun. Among the terms referred to in the Jinayat Aceh Qanun Number 6 of 2014 are Jarimah / Jinayat, Uqubat, Hudud, Ta'zir, Khamar, Maisir, Khalwat, Ikhtilath, Adultery, Sexual Harassment, Rape, Qadzaf, Liwath, Business. Students only know the term zina, sexual harassment, rape. While the Fiqh teacher knows and understands the qanun, but does not have the authority to socialize it, because the subjects in this madrasa refer to the 2017 revised 2017 curriculum, so the syllabus and lesson plans have been determined by the government based on the curriculum.